Potentials of Otherness: the Landmarks for the Foreign Country - Blažević, Zrinka (2014)
Starting from Michel de Certeau’s famous presumption that history is an emblematic form of heterology marked by a pathological effort to establish a relation with the dead and absent, this paper is aimed at questioning possible disciplinary convergences between history and imagology as exemplary discourses of/about Otherness. Following the idea of Paul Ricoeur, it may be stated that history and imagology share a common constitutive element – the image – whose readability and visibility is a key representational feature of temporal and spatial Otherness. Since both disciplines have a mediatory function with regard to the historical, social and cultural Other, the analytical focus will be on their epistemological premises, cognitive ranges and explanatory possibilities from the perspectives of tertiary paradigm, posthermeneutics and transdifference theory.
Projekt MZOS
ENG